Impact of Overactive Bladder Syndrome on Female Sexual Function - Serdar Toksöz; Taha Numan Yıkılmaz (Journal of Urological Surgery, 2015)
The etiology of female sexual dysfunction includes psychological, physiological and iatrogenic causes. Physiological and iatrogenic causes are abdominal surgery, menopause, smoking, spinal cord injuries and some antipsychotic, antihypertensive, and antidepressant drugs. When assessing sexual function, sexual function questionnaires, such as the Female Sexual Function Index, and the Sexual Function Questionnaire are used. The prevalence of female sexual dysfunction is 43% and it has been reported to increase depending on menopause and age. Estrogen, estrogen + testosterone and tibolone, PDE5, apomorphine, bupropion and flibanserin are used in the treatment of female sexual dysfunction. Overactive bladder is a disease affecting the quality of life and is characterized by urgency, frequency, nocturia and urge incontinence with especially filling phase of the bladder resulting from loss of detrusor muscle inhibition. The prevalence of overactive bladder in women in the United States has been reported to be 16.9%. Lower urinary tract symptoms and overactive bladder syndrome are not known how to cause female sexual dysfunction. Menopause and partner status were the most important predictors for female sexual dysfunction. It has been reported that overactive bladder syndrome and urinary incontinence provide prediction of development of female sexual dysfunction. Shame, fear of incontinence, and urinary incontinence as well as urge sensation during sexual intercourse in individuals with overactive bladder syndrome have been reported to be the main factors causing female sexual dysfunction. Pathophysiological relationship between the two disorders has not been elucidated and further clinical and experimental studies are needed in this regard.